The representation of the Canadian seal hunt: Analysing the rhetorical strategies of the animal rights movement and the Canadian government - Carrier-Lafontaine, Constance (University of Ottawa (Canada), 2009)
This thesis provides an analysis of textual and visual communication documents used by proponents and opponents of the Canadian seal hunt (CSH). Using a direct analysis model, as well as principles of Peircean semiotic and rhetorical analysis, the recent discourses articulated by the anti-CSH movement (International Fund for Animal Welfare and Sea Shepherd Conservation Society) and the Canadian government (Department of Fisheries and Oceans) have been considered. The findings corroborate a social constructionist perception of nature, as the rhetorical discourse focused on presenting conflicting representations of the natural world, notably the seal. It was also found that the rhetorical discourse was centred on the subsidiary themes of the representation of the kill, the sealers, and the proponents and opponents of the CSH. The thesis also notes a complementary relationship between textuality and visuality within the CSH polemic, and finds the latter being abundantly used by the anti-CSH movement but comparatively absent from the Canadian government's strategy.
Keywords: Political Science, General.; Language, Rhetoric and Composition.; Mass Communications.